Bioassay-Guided Isolation of Nigracin, Responsible for the Tissue Repair Properties of Drypetes Klainei Stem Bark - Sferrazza, Gianluca; Corti, Marco; Andreola, Federica; Giovannini, Daniela; Nicotera, Giuseppe; Zonfrillo, Manuela; Serra, Massimo; Tengattini, Sara; Calleri, Enrica; Brusotti, Gloria; Pierimarchi, Pasquale; Serafino, Annalucia (Frontiers in Pharmacology, 2020)
Drypetes klainei Pierre ex Pax is used in Cameroon by Baka people in the wound healing process and for the treatment of burns. In a previous paper we demonstrated the ability of both water (WE) and defatted methanol (DME) extracts to accelerate scratch wound closure in fibroblast cultures, thus validating the traditional use of D. klainey stem bark in the treatment of skin lesions. In this work we carried out a bioassay-guided fractionation of the most active DME, which exhibited in vitro efficacy in accelerating wound healing process, in order to isolate and identify the compound/s responsible for the assessed biological activity. HPLC was used for the metabolite profiling of DME and fractions (analytical) and for the isolation of the bioactive compound (semi-preparative). MS analyses and NMR spectroscopy were used for identifying the isolated compound. The abilities of treatments in accelerating wound healing were studied on murine fibroblasts in terms of cell viability and cell migration (scratch wound-healing assay). The results obtained allowed to unambiguously identify the isolated bioactive compound as nigracin, a known phenolic glycoside firstly isolated and characterized from bark and leaves of Populus Nigra in 1967. However, this is the first time that nigracin is identified in the Drypetes genus and that a wound healing activity is demonstrated for this molecule. Specifically, we demonstrated that nigracin significantly stimulates fibroblast growth and improves cell motility and wound closure of fibroblast monolayer in a dose-dependent manner, without any toxicity at the concentrations tested, and is still active at very low doses. This makes the molecule particularly attractive as a possible candidate for developing new therapeutic options for wound care.